2013
DOI: 10.1016/j.enpol.2013.08.084
|View full text |Cite
|
Sign up to set email alerts
|

Elasticities of gasoline demand in Switzerland

Abstract: Using cointegration techniques, we investigate the determinants of gasoline demand in Switzerland over the period . We obtain a very weak price elasticity of -0.09 in the short run and -0.34 in the long run. For fuel demand, i.e. gasoline plus diesel, the corresponding price elasticities are -0.08 and -0.27. Our rich dataset allows working with quarterly data and with more explicative variables than usual in this literature. In addition to the traditional price and income variables, we account for variables li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 34 publications
2
33
1
Order By: Relevance
“…Although the demand for gasoline is estimated income elastic, is inelastic in both bays. The speed of adjustment is low, at 28%, that of Baranzini and Weber (2013). Eltony and Al-Mutairi (1995) have argued that the demand for gasoline is the price and income inelastic in Kuwait, as development and production of oil country.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although the demand for gasoline is estimated income elastic, is inelastic in both bays. The speed of adjustment is low, at 28%, that of Baranzini and Weber (2013). Eltony and Al-Mutairi (1995) have argued that the demand for gasoline is the price and income inelastic in Kuwait, as development and production of oil country.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They showed that it is inelastic with respect to both price and income, over the short run and long run. The adjustment velocity is low, at −0.27, meaning a slow rate of adjustment to the long run equilibrium [10]. Wadud et al (2009) have obtained the elasticities in USA with cointegration technique.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although the estimated gasoline demand is income elastic, it is price inelastic in both the spans. The adjustment velocity is low, at 28%, around that of Baranzini and Weber (2013) [10] [13]. Eltony and Al-Mutairi (1995) have argued that gasoline demand is price and income inelastic in Kuwait, as a developing and oil producing country [15].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations